Avaliação do uso combinado da imunização ativa com MAB 10.D7 e passiva com MAB 3F12E7 em modelo de melanoma murino B16F10 - Hamaguchi, Barbara [UNIFESP] (2019)
Melanoma is an aggressive and lethal type of cancer which requires new approaches to be effectively treated. Angiogenesis-directed immunotherapy may contribute to refrain tumoral growth and metastization. Our group has successfully developed two monoclonal antibodies (mAb): 3F12E7, which recognizes fibroblast growth factor 2 (FGF2), and 10.D7 that interferes with vascular endothelial growth factor (VEGF) activity, both showing promising results in combating tumoral development. Objective: To verify the existence of combining effects in combining both mAbs over B16F10 tumor growth inhibition. Methods: Groups of C57Bl/6 mice were actively immunized twice with a sevenday interval with either mAb 10.D7 or irrelevant mAb conjugated with KLH. Ten days after the second immunization, mice were subcutaneously inoculated with B16F10 cells. Thereafter, mice were treated with either mAb 3F12E7 or irrelevant antibody by intraperitoneal injection, for five consecutive times every 48 hours. The animals had their sera collected for evaluation of VEGF-binding antibodies on immunization, inoculation and euthanasia days, and tumor volume was measured daily. After euthanasia, tumors were excised and histological sections evaluated for the presence of necrosis and CD31+ vessels. Results: Mice treated with 10.D7/3F12E7 presented the lowest tumoral volumes and greater delay on tumor establishment when compared to the other groups of treatments. Also, the smallest tumors were found in those animals with higher levels of VEGF-binding antibodies. Higher necrosis rates were observed in groups 10.D7/Irrelevant and 10.D7/3F12E7, which was inversely proportional to the presence of CD31+ vessels. Data were compared by means of one-way ANOVA test, p <0.05. Conclusion: There is a combined effect on the inhibition of tumor development when immunizations with mAbs 10.D7 and 3F12E7 are associated.